# How do you find the derivative of #(x^3-3x^2+4)/x^2#?

Using the quotient rule, which states that

Applying the rule:

By signing up, you agree to our Terms of Service and Privacy Policy

To find the derivative of (\frac{{x^3 - 3x^2 + 4}}{{x^2}}), you can use the quotient rule. The quotient rule states that if you have a function in the form (\frac{{f(x)}}{{g(x)}}), then the derivative is given by (\frac{{f'(x)g(x) - f(x)g'(x)}}{{[g(x)]^2}}).

Let (f(x) = x^3 - 3x^2 + 4) and (g(x) = x^2). Then, (f'(x) = 3x^2 - 6x) and (g'(x) = 2x).

Now, applying the quotient rule, we get:

[ \frac{{d}}{{dx}}\left(\frac{{x^3 - 3x^2 + 4}}{{x^2}}\right) = \frac{{(3x^2 - 6x)(x^2) - (x^3 - 3x^2 + 4)(2x)}}{{(x^2)^2}} ]

Simplify this expression to find the derivative.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the derivative of #f(x)=e^(2x) ln(x+2)#?
- How do you find the derivative of #y=arcsin(5x+5)#?
- How do you differentiate #f(x) = sqrt(sin^3(2-x^2) # using the chain rule?
- Let r(x)=f(g(h(x))), where h(1)=2, g(2)=3, h'(1)=4, g'(2)=5, and f'(3)=6, how do you find r'(1)?
- Let #f(x)=( lne^2x)/x-1# for x>1. If g is the inverse of f, then what is g'(3)?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7